Subsurface carbon monoxide oxidation capacity revealed through genome‐resolved metagenomics of a carboxydotroph. Issue 5 (23rd July 2020) - Mu, Andre; Thomas, Brian C.; Banfield, Jillian F.; Moreau, John W.
Summary: Microbial communities play important roles in the biogeochemical cycling of carbon in the Earth's deep subsurface. Previously, we demonstrated changes to the microbial community structure of a deep aquifer (1.4 km) receiving 150 tons of injected supercritical CO2 (scCO2 ) in a geosequestration experiment. The observed changes support a key role in the aquifer microbiome for the thermophilic CO‐utilizing anaerobe Carboxydocella, which decreased in relative abundance post‐scCO2 injection. Here, we present results from more detailed metagenomic profiling of this experiment, with genome resolution of the native carboxydotrophic Carboxydocella . We demonstrate a switch in CO‐oxidation potential by Carboxydocella through analysis of its carbon monoxide dehydrogenase (CODH) gene before and after the geosequestration experiment. We discuss the potential impacts of scCO2 on subsurface flow of carbon and electrons from oxidation of the metabolic intermediate carbon monoxide (CO).